Systematic Literature Review (SLR): Kepemimpinan Situasional dalam Industri Penerbangan - Siregar, Gusnia Khairunnisa; Surtiningtyas, Sri Rahayu (Jurnal Bisnis dan Operasi Penerbangan, 2024)
This research aims to understand the role of situational leadership in the aviation industry and how this can contribute to safety and operational efficiency. The aviation industry is a dynamic and complex sector, requiring effective management in facing various challenges and exploiting opportunities. One approach that has proven effective in this industry is situational leadership, where the leader adapts his leadership style to the team's level of readiness and competency in dealing with a particular situation. The research method used is Systematic Literature Review (SLR), by collecting data from various previous studies to understand best practices in situational leadership that can be applied in the aviation industry. The research results show that situational leadership can help improve flight safety with appropriate responses to emergency or stressful situations that arise during flights. Additionally, by adapting his or her leadership style to suit different operational situations, leaders can guide teams more effectively, increasing overall operational efficiency. In conclusion, situational leadership can be an effective tool in improving safety and operational efficiency in the aviation industry. By understanding and implementing best practices in situational leadership, airlines can optimize their performance and maintain a competitive position in the marketplace.